Ensino Religioso nas escolas municipais de Cascavel-Paraná: uma análise histórica - Kunzler, Flávia Paim (2018)
The present research aims to investigate the historical process of how Religious Education was institutionalized in public schools in Cascavel – PR. For the production of this study, a bibliographic research related to the philosophical principles of religion was used, especially in what is concerned to the classical authors, that mostly affected and still affect the debate regarded to our society. The historical aspects of how the Religious Education was institutionalized in Brazil and in Paraná were studied in order to comprehend the main elements that have influenced this historical process in Cascavel. Besides the classical authors, this work seeks theoretical support in official documents issued by the União, the State of Paraná, by AMOP (Associação dos Municípios do Oeste do Paraná), Secretaria Municipal de Educação de Cascavel, by public schools and others, including personal files, which, in some way, record the instructions that support the offer of Religious Education in public schools from Cascavel. This analysis was based in a historical perspective that attempts to understand religion as the product and the producer of human relations, in a contradictory context, in which the Religious Education comes from a process of battling political, cultural, ideological and social interests. From a dialectical perspective, it verified the historical determinations about Religious Education’s debate that, in the middle of the process of Cascavel’s city development in Religious Education, was predominated by Christian beliefs, Catholic mostly, whereas other beliefs were outshined. He also found that Religious Education in its guidelines, rather than a perspective of the formation of the integral man, focused on the institutionalization of the law of the Bourgeois State. Thus, it sought to guarantee the right to religious teaching, as well as respect for religious diversity.